Deoxyribonucleic Acid Photonic Wires with Three Primary Color Emissions for Information Encryption. (28th February 2021) - Yang, Fei Fan; Li, Chun Hong; Lv, Wen Yi; Zhen, Shu Jun; Huang, Cheng Zhi
Abstract: DNA photonic wires (PWs) are a new type of photon delivery nanodevice and have attracted wide attention due to their excellent photon delivery ability via Förster resonance energy transfer (FRET) but are dramatically challenged in real applications. In this study, 7‐amino‐4‐methyl‐3‐coumarinylacetic acid is used as a donor, Texas Red is used as an acceptor, and acridine orange is used as a bridge to intercalate DNA to facilitate the homo‐FRET process, which leads to DNA PWs with high‐energy transfer efficiencies (≈0.9). Notably, the newly developed DNA PWs exhibit characteristic emissions in the three primary colors, which are successively adjusted by simply changing the extent of FRET to make over 36 subtypes of fluorescence emissions. This polychroism is further applied for information encryption with high efficiency, which is a new application for DNA PWs. Abstract : Noble donor(D)‐bridge(B)‐acceptor(A) DNA photonic wires (PWs) are constructed, which have superior Förster resonance energy transfer (FRET) efficiencies (≈0.9) and three primary colors (RGB) emissions via three kinds of fluorophore. By adjusting the extent of FRET, 36‐color DNA PWs are developed and successfully applied to the information encryption field.